New triarylpyrazoles as broad-spectrum anticancer agents: Design, synthesis, and biological evaluation - El-Gamal, Mohammed I.; Park, Yi Seul; Chi, Dae Yoon; Yoo, Kyung Ho; Oh, Chang-Hyun (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2013)
A new series of diarylureas and diarylamides possessing 1,3,4-triarylpyrazole scaffold was designed and synthesized. Their in vitro antiproliferative activities against NCI-60 cell line panel were tested. Most of the compounds showed strong and broad-spectrum antiproliferative activities. Compound 18 exerted sub-micromolar IC50 values over all the subpanels of nine different cancer types. Its IC50 value over MDA-MB-435 melanoma cell line was 27 nM. Compounds 10-13, 22, and 23 possessing urea spacer exerted lethal effect over the NCI-60 panel with mean %inhibitions more than 100% in single-dose testing. Compounds 13 and 23 with urea linker and 3',5'-bis(trifluoromethyl)phenyl terminal ring showed the highest mean %inhibition over the NCI-60 panel in single-dose testing, and showed high potencies and broad-spectrum anticancer activities in five-dose testing. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: MELANOMA-CELL LINE; ANTIPROLIFERATIVE ACTIVITY; 1,3,4-TRIARYLPYRAZOLE SCAFFOLD; DERIVATIVES; DIARYLAMIDES; DIARYLUREAS; DISCOVERY